2011
DOI: 10.1021/jp111099g
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of C2H4, CO, and H2 on Clean and Graphite Carbon-Modified Co(0001) Surfaces

Abstract: Chemisorption and surface reactions of C2H4, CO, and H2 on clean and graphite carbon-modified Co(0001) surfaces have been investigated by thermal desorption spectroscopy, X-ray photoelectron spectroscopy, and low-energy electron diffraction. The chemisorption and decomposition behaviors of C2H4 depend largely on the vacant sites available on clean Co(0001) at 130 K. C2H4 chemisorbs dissociatively to produce C2H2(a) and H(a) at low exposures but both dissociatively and molecularly to produce C2H4(a), C2H2(a), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 54 publications
6
29
0
Order By: Relevance
“…On Co(0001) the adsorption of H 2 has been shown to occur dissociatively at temperatures as low as 130 K, producing typical second-order-kinetics desorption peaks between 300-450 K in TPD spectra. 60,61 A similar behaviour is also observed on the same low index plane when D 2 is used instead of H 2 . 46,62 DFT calculations for all surface coverages indicate that the most stable site for H on Co(0001) is the three-fold hollows, with fcc hollows slightly favoured over hcp hollows.…”
Section: Cobalt Single Crystal Studiessupporting
confidence: 65%
“…On Co(0001) the adsorption of H 2 has been shown to occur dissociatively at temperatures as low as 130 K, producing typical second-order-kinetics desorption peaks between 300-450 K in TPD spectra. 60,61 A similar behaviour is also observed on the same low index plane when D 2 is used instead of H 2 . 46,62 DFT calculations for all surface coverages indicate that the most stable site for H on Co(0001) is the three-fold hollows, with fcc hollows slightly favoured over hcp hollows.…”
Section: Cobalt Single Crystal Studiessupporting
confidence: 65%
“…limit the discussion to the main findings, thereby highlighting the crucial role of co-adsorbed CO on the surface chemistry of FTS surface intermediates. In brief, ethylene was dosed onto the Co(0001) surface held at 100 K and heated to 200 K afterwards to produce 0.12 ML acetylene + 0.24 ML H ad [24,66,68]. The infrared absorption spectrum after heating to 250 K, plotted in Fig.…”
Section: The Surface Chemistry Of Growing Chains: Experiments and Theorymentioning
confidence: 99%
“…Great efforts have been devoted to understanding the CO activation and carbon chain propagation mechanisms, but the results are of ongoing debate . Only a few experimental studies have been reported on the reactivity of carbidic carbon, atomic oxygen, and atomic hydrogen on Co surfaces …”
Section: Figurementioning
confidence: 99%
“…Therefore, it is crucial to understand the fundamental processest aking place on Co surfaces during FT synthesis, in order to optimize the design of Co FT catalysts essential for the efficient use of the metal. [13][14][15][16][17][18][19][20] We previously reported that the carbidic carbon species on aC o(0001)s urfacetransformsi nto the graphitic carbon species at elevated temperatures. [10][11][12] Only af ew experimental studies have been reported on the reactivity of carbidic carbon, atomic oxygen, and atomic hydrogen on Co surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation